The hydrodynamic function of shark skin and two biomimetic applications - Oeffner, J.; Lauder, G. V. (The Journal of Experimental Biology, 2012)
Streamlined sharks are legendary for their effortless swimming. George Lauder from Harvard University explains that the fish have long inspired human engineers, but more recently attention has focused on how the fish`s remarkable skin boosts swimming. Coated in razor sharp tooth-like scales, called denticles, the skin is thought to behave like the dimples on a golf ball, disturbing the flow of water over the surface to reduce the drag. But something didn`t quite sit right with Lauder.`All of the shark skin studies were done on flat shark skin mimics that were held straight and immovable. But shark skin moves`, recalls Lauder. So, when Masters student Johannes Oeffner joined his lab, Lauder suggested that they take a look at the fluid dynamics of shark skin and its analogues to find out how the fish`s motion affects fluid flowing over the rough surface (p. 785).